HUSBAND SUPPORT, ADVERSITY QUOTIENT, AND ANXIETY OF PRIMIGRAVIDA THIRD-TRIMESTER PREGNANT MOTHERS - Avifurohmah, Khoridatul; Mariyati, Lely Ika; Fahmawati, Zaki Nur (Jurnal Psikologi, 2023)
This current study aims to investigate the negative relationship between husband’s support, adversity quotient,and anxiety of third-trimester primigravida pregnant mothers. A quantitative method with a cross-sectional study design was employed. A total of 103 primigravida third-trimester mothers (Mean age = 27.02) who received prenatal care at the Sidoarjo health center was participated in this study. Data were collected using the Husband’s Support Scale (51 items, α = .96), the Adversity Quotient Scale (39 items, α = .93), and the Anxiety Scale of the Pregnant Mother (49 items, α = .92). Data analysis was conducted using the Multiple Linear Regression analysis with the assistance of SPSS version 24 for Windows. The results indicate negative relationships between husband’s support (r =-.581, p <.001) and adversity quotient (r = -.612, p <.001) with anxiety. The husband’s support and adversity quotient are together explaining 37.9% variances of anxiety in primigravida third-trimester mothers (Adj. R2 = .379; F(32, 100) = 32.07, p < .001). This research implies the importance of husband support for pregnant mothers and the need for mothers to develop adequate adversity quotient to manage pregnancy related anxiety.